Measurements of differential cross sections for associated production of a W boson and jets in proton-proton collisions at $\sqrt{s} =$ 8 TeV - CMS collaboration (2261 authors) (2017)
Differential cross sections for a W boson produced in association with jets are measured in a data sample of proton-proton collisions at a center-of-mass energy of 8 TeV recorded with the CMS detector and corresponding to an integrated luminosity of 19.6  fb−1. The W bosons are identified through their decay mode W→μν. The cross sections are reported as functions of jet multiplicity, transverse momenta, and the scalar sum of jet transverse momenta (HT) for different jet multiplicities. Distributions of the angular correlations between the jets and the muon are examined, as well as the average number of jets as a function of HT and as a function of angular variables. The measured differential cross sections are compared with tree-level and higher-order recent event generators, as well as next-to-leading-order and next-to-next-to-leading-order theoretical predictions. The agreement of the generators with the measurements builds confidence in their use for the simulation of W+jets background processes in searches for new physics at the LHC.